PENGARUH EFFECTIVE TAX RATE DAN KARAKTERISTIK PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Raya Siahaan, Christian Vieri; Siringo-Ringo, Eko Deswin Miechaels; Sirait, Sarida; Nathania, Beatrice (Politeknik Bisnis Indonesia, 2025)
This research aims to analyze the influence of Effective Tax Rate (ETR), Company Size, Growth Rate, and Profitability on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange during the period of 2018-2022. This study uses a quantitative approach with secondary data obtained from the annual financial reports of manufacturing companies. Using purposive sampling, 150 data were analyzed. The data analysis techniques used include descriptive statistical analysis, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination, and partial hypothesis test (t-test) and simultaneous hypothesis test (F-test). The results showed that the Effective Tax Rate has no significant effect on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange for the period 20182022, with a significance value of 0.419 > 0.05. Company Size has a significant effect on the capital structure with a significance value of 0.006 < 0.05. Growth Rate has no significant influence with a significance value of 0.532 > 0.05, while Profitability has a significant effect with a significance value of 0.00 < 0.05. Simultaneously, Effective Tax Rate, Company Size, Growth Rate, and Profitability have a significant effect on the capital structure with an F-calculated value of 56.485 and a significance level of 0.000 < 0.05. The Adjusted R Square value of 0.598 indicates that 59.8% of the variation in capital structure can be explained by these four variables, while 40.2% is influenced by other variables not examined in this study.